Policy-implementation dynamics of national housing programmes in India - evidence from Madhya Pradesh - Mitra, Sheuli (International journal of housing policy, 2022)
The supply of housing, particularly for lower economic households, remains a major challenge in India. Given the vast scale and diversity of the country, implementation of centrally administered housing programmes occurs in varying local contexts, giving rise to significant variations in development on the ground. This research focuses on the ongoing Housing for All 2022 (PMAY) programme, which, with its combination of mass housing as well as assisted self help housing components, claims to address India's housing shortage in a holistic manner. Statistics on the physical progress of implementation of the PMAY, rank Madhya Pradesh, one of the lesser urbanised states, among the top five states of the country. In this study, the components and structuring of the programme are compared with the experience on implementation from stakeholders and beneficiaries in selected towns of Madhya Pradesh. While the big-city bias of housing programmes is well researched, this case investigates implementation hurdles and means of negotiating them in small and medium towns of India. The paper argues the need to appropriately structure national housing programmes and embed a dialogue between the Centre, State and Urban Local Bodies, to enable context specific implementation for effectively ameliorating the housing shortage of the urban poor.